Asymmetric pathology in primary progressive aphasia with progranulin mutations and TDP inclusions. (16th February 2016) - Kim, Garam; Ahmadian, Saman S.; Peterson, Melanie; Parton, Zach; Memon, Rohail; Weintraub, Sandra; Rademaker, Alfred; Bigio, Eileen; Mesulam, M.-Marsel; Geula, Changiz
Abstract : Objective: To investigate quantitative regional distribution and hemispheric asymmetry of TDP-43 (TAR DNA-binding protein 43) inclusions, neurons, and activated microglia in primary progressive aphasia (PPA) with progranulin ( GRN ) mutations, and to determine concordance between distribution of pathology, clinical phenotype, and known atrophy patterns. Methods: Antibodies to phospho–TDP-43, NeuN (neuronal nuclei), and HLA-DR were used to visualize inclusions, neurons, and activated microglia in paraffin-embedded tissue sections from 4 participants with PPA: 2 of the agrammatic and 2 of the logopenic subtype. Unbiased stereological counting techniques were used for quantitation of immunoreactive profiles in language- and memory-related cortical areas bilaterally. Patterns of pathology across cortical areas and hemispheres were compared and their relationships with known patterns of atrophy investigated. Results: Numerical densities of TDP-43 inclusions, and less so of activated microglia, were greater in language-related areas compared with memory-related areas. In language areas, neuronal density displayed a pattern opposite to inclusions and activated microglia. Densities of inclusions and microglia were greater ( p < 0.05), and densities of neurons were lower ( p < 0.005), in the left hemisphere compared with the right. In agrammatic PPA, the highest densities of TDP-43 inclusions were observed in left inferior or middle frontal gyri, and in logopenic participants, the highest density of inclusions was seen in left inferior parietal lobule. This distribution is consistent with subtype-specific peak atrophy sites. Conclusions: Distribution of TDP-43 inclusions and neurons, and to a smaller extent of activated microglia, show a regional and hemispheric pattern consistent with disease phenotype and known patterns of atrophy in PPA with GRN mutations.